Counselling training for speech–language therapists working with people affected by post‐stroke aphasia: a systematic review. Issue 3 (13th February 2019) - Sekhon, Jasvinder K.; Oates, Jennifer; Kneebone, Ian; Rose, Miranda
Abstract: Background: Speech–language therapists use counselling to address the psychological well‐being of people affected by post‐stroke aphasia. Speech–language therapists report low counselling knowledge, skill and confidence for working in post‐stroke aphasia which may be related to a lack of counselling training specific to the needs of this client group. Aims: To identify current training in counselling for speech–language therapists to address psychological well‐being in people affected by post‐stroke aphasia. Specifically, the intent was to establish the objectives, content, amount, teaching methods and outcomes of counselling training provided to speech–language therapists working with people affected by post‐stroke aphasia. Methods & Procedures: Eleven databases were searched from inception to January 2018 using terms relating to counselling, psychological well‐being, speech–language therapy, stroke, aphasia and training. Studies using any research methodology and design were included. Nine studies were critically appraised and synthesized as a systematic review using the Search, AppraisaL, Synthesis and Analysis (SALSA) framework. Main Contribution: Information on counselling training came from the UK, United States and Australia. Student speech–language therapists received training in goal‐setting and generic counselling skills. After qualification, speech–language therapists received counselling training from mental health professionals within stroke workplaces, from external providers and further education. A range of teaching techniques and counselling approaches were described. Self‐report and themes from qualitative data were the primary measures of counselling training outcomes. Moderate correlations were reported between counselling training and levels of speech–language therapists' knowledge, comfort, confidence and preparedness to counsel people affected by post‐stroke aphasia. Conclusions: Research in counselling training for speech–language therapists working in post‐stroke aphasia is limited, with a small number of primarily low‐quality studies available. Training in generic counselling skills and brief psychological approaches with support from mental health professionals in the stroke workplace enabled speech–language therapists to feel knowledgeable, skilled and confident to address the psychological well‐being of people affected by post‐stroke aphasia. Evidence about the effectiveness of counselling training on speech–language therapists' confidence and competence in practice and on client outcomes in psychological well‐being in post‐stroke aphasia is required.